A CdZnTe-based high-resolution gamma spectrometer for in-situ measurement in the marine environment. (1st October 2022) - Zhou, Z.; Feng, C.; Zhao, M.; Wang, X.; Li, L.; Jiang, Z.; Wang, Y.; Yuan, J.; Cao, P.; An, Q.
Abstract: In-situ radiation measurement and radionuclide identification in the ocean provide essential information for seabed geological and marine ecological exploration. In this work, a small-sized CdZnTe-based gamma spectrometer with high energy resolution was designed for automatic in-situ radioactivity measurement in the marine environment down to a depth of 4500 m. Four 10 × 10 × 5 mm 3 CdZnTe detectors were used, and their energy spectra were combined to improve the detection efficiency. Instead of multi-stage analog circuits, digital processing methods such as digital filter, trigger, and energy calculation were implemented in the readout electronics to improve compactness and reduce the power consumption of the spectrometer. Monte Carlo simulations were carried out to estimate the gamma attenuation through the waterproof shell and the marine efficiency of the spectrometer. Several gamma sources and samples were used to evaluate the nuclide identification capability of the spectrometer. The resolution (FWHM) of the spectrometer was 1.8% at 662 keV at room temperature and improved to 1.5% at about 3°C, which is close to the ambient temperature in the ocean. The spectrometer was tested under a pressure of up to 58 MPa and was used for marine measurement at a depth of 1418 m in the South China Sea. The radioactivity of the subsea region is higher than that of seawater, where thorium daughters, radon daughters, and ^40K were identified in the spectrum result.